Investigation and Process Parameter Optimization on Wire Electric Discharge Machining of Aluminium 6082 Alloy. (24th September 2022) - Murali, G.; Murugan, M.; Arunkumar, K.; Elumalai, P. V.; Mohanraj, D.; Prabhakar, S.
Abstract : Wire electrical discharge machining (WEDM) is an unconventional machining process that is being extensively used in the aerospace, medical devices, die, tooling, and automotive industries for machining high-hardness materials with conductivity. In the present work, WEDM of aluminium 6082 alloys was carried out since it influences diversified applications in manufacturing industries. The WEDM process includes an extensive number of variables that influence its execution. However, based on the literature survey, three process parameters such as pulse-on time (PTON ), pulse-off time (PTOFF ), and wire feed (WF) were taken into consideration. The factorial design was used for the selection of parameter levels and arrived at the 27 trails for the machining. The output responses of the WEDM, namely, surface roughness (SR), kerf width (KF), and metal removal rate (MRR) were measured, and its parameter optimization was also carried out to minimize the significant effect on productivity and the quality of components. The measured output response was compared with the predicted response surface methodology (RSM) results; it was found that the SR and KF values decreased with the increase of PTON . The MRR was increased with the increase of PTON .